Protection of Spiritual Rights in Sharia Dispute Resolution: Sustainable Finance Policy - Trisiana Dewi; Triyono Adi Saputro (IECON: International Economics and Business Conference, 2025)
This research study explores safeguarding spiritual rights within the framework of Sharia dispute resolution mechanisms, particularly in the context of sustainable finance policies. Spiritual rights and spiritual protection are crucial in ensuring legal, moral, and spiritual justice in conflict resolution based on Sharia principles. Shariah-compliant dispute resolution is predicated on the notion that spiritual protection constitutes an integral component of individual and community rights. This component, in turn, significantly influences social and economic sustainability. Integrating ethical values, justice, and spiritual protection within sustainable finance policies that adopt Shariah principles strengthens dispute resolution mechanisms. The process employs various dispute resolution methods, including Sharia mediation, deliberation, and arbitration, to preserve harmony and balance among society's economic, social, and spiritual dimensions. This study underscores the significance of safeguarding spiritual rights in fortifying the legitimacy and efficacy of dispute resolution mechanisms within a Shariah-compliant sustainable financial system. The integration of spiritual safeguards within Shariah-compliant sustainable finance policies has been demonstrated to enhance the trust of the involved parties in the dispute resolution process, thereby contributing to the establishment of a fair and sustainable financial environment. The practical implication of this research is that it will determine whether a dispute resolution model that prioritizes the protection of spiritual rights and Sharia compliance contributes to developing an inclusive and sustainable financial system.